DETEKSI DINI DAN EDUKASI MENGENAI PERAN FISIOTERAPI PADA SCOLIOSIS DI POLI REHAB MEDIK RSUD SALATIGA - Athiyaturrofi, Alifah; Supriyadi, Arin; Yanuar, Reza Arshad (LPPM Institut Pendidikan Nusantara Global, 2024)
People in general still think that scoliosis is not a big problem. In fact, the effects of scoliosis itself are not small; they can carry risks such as unstable balance and musculoskeletal disorders. If left too long, it will cause various problems, namely pain, cosmetically disturbing deformities, functional obstacles, lung problems, the possibility of progression into adulthood, and psychological disorders. This activity aims to introduce what scoliosis is and provide education about the role of physiotherapy to patients at the Medical Rehab Clinic at Salatiga Regional Hospital. After carrying out community service on November 16, 2023, the results showed that patient knowledge about scoliosis and the role of physiotherapy in scoliosis increased. This activity is provided in the form of community service, where the participants are patients of the Medical Rehab Polyclinic at Salatiga Regional Hospital. The education provided is in the form of early detection and education regarding the role of scoliosis physiotherapy. Based on the data obtained, the counseling that has been given has had a positive impact on patient knowledge; this can be seen in the enthusiasm and question-and-answer process. The author hopes that this service will continue to have a positive impact on patients and that patients will always maintain their posture with the exercises that have been taught